Os pronomes demonstrativos do Português Brasileiro na fala e na escrita - Jungbluth, Konstanze (Cadernos de Linguagem e Sociedade, 2010)
The aim of this paper is to propose a system of the demonstrative pronouns in Brazilian Portuguese within the broader context of the other Romance languages. The results of the qualitative research show important differences between the spoken and the written variety. Thus a double-faced systematization is developed. The multi-faceted process of reduction and re-establishment from two- to three-terms-paradigms and vice-versa from Latin to neo-latin languages, esp. from Portuguese to Brazilian Portuguese might be of interest not only for linguists working on Romance Languages but also for those interested in typology, language change and processes of grammaticalization.